Catalytic reforming of biomass pyrolysis gas over Ni catalysts: alumina, spent fluid catalytic cracking catalyst and char as supports - Low, Ching Wei (2025)
The potential replaceability of a Ni catalyst supported on commercial α-Al2O3 (Ni/Al2O3) by Ni on biomass-derived char (Ni/Char), and Ni on spent fluid catalytic cracking catalyst (Ni/FCC) for steam reforming of biomass pyrolysis gas was investigated (14 h at 850°C, steam/carbon ratio = 5). The catalysts reformed 60–80 % of C2-C5 hydrocarbons, producing 2.7–4.1 mg min−1 of H2. The reforming activity of Ni/Al2O3 and Ni/FCC was higher compared to Ni/Char, indicating the beneficial role of metal oxide supports. The use of Al2O3 and FCC resulted in a lower thermo-oxidative stability of coke formed on Ni/Al2O3 and Ni/FCC compared to Ni/Char. Furthermore, the deposited Ni showed higher stability towards oxidation by steam into NiO in case of Al2O3 and FCC compared to char. According to reforming activity, H2 production rate, coking, and Ni oxidation of the catalysts, FCC has better prospects as an alternative support in a reforming catalyst than char.